2015
DOI: 10.1149/2.0191503jss
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of GaN CMP Based on H2O2Slurry Combined with UV Light

Abstract: Chemical mechanical polishing (CMP) of GaN(0001) with a H2O2-SiO2-based slurry is investigated in this paper. The result shows that an atomically flat surface with a roughness of 0.065 nm is obtained after polishing. Compared with a SiO2-based slurry, the H2O2-SiO2-based slurry can realize a higher material removal rate (MRR) and a better surface quality with less scratches. The pH value mainly affects the mean particle size of SiO2 and the chemical environment of the corrosion reaction with H2O2, resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Over the past, the studies on CMP slurries for GaN were focused on various abrasives particles (Al 2 O 3 and SiO 2 ) and chemical oxidizers-KOH, sodium-hypochlorite, H 2 O 2 and KMnO 4 [22][23][24][25][26][27][28][29]. Recently, CMP studies [28] on (0001) GaN with slurry having KMnO 4 as an oxidizer indicate that the MRR for Al 2 O 3 (as abrasive) containing slurry is significantly higher (~double) than that for the slurry having SiO 2 (as abrasive).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Over the past, the studies on CMP slurries for GaN were focused on various abrasives particles (Al 2 O 3 and SiO 2 ) and chemical oxidizers-KOH, sodium-hypochlorite, H 2 O 2 and KMnO 4 [22][23][24][25][26][27][28][29]. Recently, CMP studies [28] on (0001) GaN with slurry having KMnO 4 as an oxidizer indicate that the MRR for Al 2 O 3 (as abrasive) containing slurry is significantly higher (~double) than that for the slurry having SiO 2 (as abrasive).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Besides, Zhang et al [36] observed a phase transformation phenomenon of the silicon substrate polished by a diamond abrasive. However, these previous studies only focused on the nanoscale level of deformation and material removal despite prior experimental researches have reported the sub-nanoscale of polishing [15][16][17]. In particular, hardly any studies have carefully considered the sub-nanoscale deformation and removal in spite of its central role in creating an ultra-smooth surface.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [16] obtained a smoother 0.0518 nm surface roughness and a better MRR of 66.9 nm/h by using a metal catalyst in an acidic slurry. Besides, Wang et al [17] reported an excellent 0.065 nm surface roughness and a high MRR of 103 nm/h by using H2O2-SiO2-based slurry. While Nelabhotla et al [18] achieved a higher MRR of 142 nm/h by optimizing the CMP parameters in a KMnO4/Al2O3 slurry.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [31] obtained an atom-level smooth surface with a material removal rate of 120 nm/h. Using ultraviolet light to promote oxidation of the material, Wang et al [32] performed chemical mechanical polishing with H 2 O 2 in combination with SiO 2 as a polishing slurry, and found that this method improved the polishing efficiency. Ye et al [33] added an UV LED (Light-emitting diode) system to the chemical mechanical polishing system of 4H-SiC wafers, and achieved higher material removal rates and atomically smooth surfaces.…”
Section: Introductionmentioning
confidence: 99%